PENERAPAN PEMBERIAN TERAPI SLOW STROKE BACK MASSAGE DALAM MENURUNKAN TEKANAN DARAH DI PERUMAHAN KRANGGAN PERMAI JATISAMPURNA - Ridha Tiomanta Purba, (2022)
Hypertension is one of the risk factors for cardiovascular disease or heart disease such as stroke, other heart diseases such as heart attack and heart failure, as well as kidney disease. The purpose of this study was to determine the effectiveness of the application of slow stroke back massage therapy in lowering blood pressure. The subjects of this study were two patients with hypertension, with 1 patient being managed and 1 patient being resumed. The measuring instrument for this study uses a sphygmomanometer to measure blood pressure before and after the intervention. The measurement results prove that there is a decrease in blood pressure in hypertensive patients. The conclusion in this study is that slow stroke back massage therapy has an effect on reducing blood pressure.